A Hard Day's Night: Diatoms Continue Recycling Photosystem II in the Dark - Li, Gang; Woroch, Amy D.; Donaher, Natalie A.; Cockshutt, Amanda M.; Campbell, Douglas A. (Frontiers in Marine Science, 2016)
Marine diatoms are photosynthetic, and thrive in environments where light fluctuates. Like all oxygenic photosynthetic organisms diatoms face a light-dependent inactivation of the Photosystem II complexes that photooxidize water to generate biosynthetic reductant. To maintain photosynthesis this photoinactivation must be countered by slow and metabolically expensive protein turnover, which is light dependent in cyanobacteria and in plants. We tracked daily cycles of the content, synthesis and degradation of Photosystem II, in a small and in a large marine diatom, under low and high growth light levels. We show that, unlike plants, diatoms maintain extensive cycling of Photosystem II proteins even in the dark. Photosystem II protein cycling saturates at low light, and continued cycling in dark periods, using energy from respiration, allows the diatoms to catch up to excess photoinactivation accumulated over the preceding illuminated period. The large diatom suffers only limited photoinactivation of Photosystem II, but cycling of Photosystem II protein exceeds Photosystem II inactivation, so the large diatom recycles functional Photosystem II units before they are inactivated. Through the diel cycle the contents of active Photosystem II centers and Photosystem II proteins change predictably, but are not correlated, generating large changes in the fraction of total PSII that is active at a given time or growth condition. We propose that dark and steady cycling of Photosystem II proteins is driven by the tight integration of chloroplastic and mitochondrial metabolism in diatoms. This ability for baseline, continuous Photosystem II repair could contribute to the success of diatoms in mixed water environments that carry them from illumination to darkness and back.